Kepemimpinan Inovatif Kepala Madrasah dalam Meningkatkan Kualitas Lembaga Pendidikan Islam di MTs Negeri 2 Deli Serdang - Nurhayati, Suci; Budi, Budi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study was motivated by the important role of madrasa principals as innovators in improving the quality and competitiveness of Islamic educational institutions amid rapid educational changes. Madrasa principals are not only responsible for managerial functions but are also expected to create innovations relevant to contemporary educational needs. This research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation at MTsN 2 Deli Serdang. The research subjects consisted of the madrasa principal and teachers. The findings revealed that innovations had been implemented comprehensively in religious programs, academic development, teacher professionalism, learning technology, and extracurricular activities. These innovations were supported by participatory leadership, strong collaboration among school members, and adequate facilities, although several obstacles were found, particularly related to the technological competence of some teachers. Overall, these innovations positively influenced the quality of learning, teacher professionalism, student motivation, the strengthening of Islamic character, and the overall quality of the institution.